Head Injury Analysis of Bus Rollover Occupants for Various Seat Restraint Systems and Locations - Caesario (NIM : 13113147), Elbert
Population growth in Indonesia is continuing to rise. Thus, the uses of public transport is increasing. Unfortunately, occupant safety in Indonesian public transport system, especially bus, is still an issue. Bus accident still tend to happens in Indonesia. Of all types of accident, bus rollover is the one that has the most fatalities. To this day there is no regulation that governs any bus safety aspect in Indonesia. This research was done by simulating bus structure based on UNECE R66 regulation. Dummy was used to realistically simulating occupant movement when rollover occurs. This research was aimed to find the value of HIC due to bus rollover. Probability of severe head injury will increase when HIC value surpasses 700. The simulations consisted of various parameters of dummy seat position and the uses of seat restraint system. The simulations show that the highest HIC value is caused by the impact that occured between dummyÃ‚Â’s head and the ground. The impact happens when dummy is seated near to rollover direction. Lap seatbelt is failed to prevent head-ground impact in one of the seat position. However, combination of lap and shoulder seatbelt is able to prevent such impact. The simulations of bus rollover on the flat surface show the highest HIC value when dummy is not using seat restraint system.